Administrative Division within the August 2018 Project and the Introductory Draft of the Algerian Regional Communities Law - Meliani, Saliha (Journal of Legal Studies and Researches, 2020)
The study aims to examine the system of administrative district how his developed by the Algerian legislature by decrees 2015 and 2018 respectively, as well as the new administrative divisions drawn up by the preliminary draft Regional Community Law, which will be a substitute for the existing municipal and state laws. Especially in light of Blurring parameters of this division and the object from it’s. What distinguishes the new administrative units especially the ones created in the introductory project, is that they have a different nature to the other administrative divisions, justifying their existed for the promotion of public service in the local space and ensuring continuous development of the regions. Is this motivation enough?